Murder with chocolate tea : a Daisy's Tea Garden mystery - Smith, Karen Rose (Smith, Karen Rose. Daisy's Tea Garden mysteries., 2023)
When an anonymous tip during a true crime podcast reveals clues to a 20-year-old unsolved murder, tea shop owner and bride-to-be Daisy Swanson suspects a connection between a current homicide and this cold case, setting out to solve it before she walks down the aisle.